Temporal Variation Of Amphibians On Gunung Raya, Pulau Langkawi, Kedah, Peninsular Malaysia - Ehwan Ngadi; J.Nur Johana; M.N.Shukor; L.L. Grismer; Y. Salmah; A.Norhayati (MALAYSIAN NATURE SOCIETY, 2024)
Malayan Nature Journal,Volume 74 Issue 4 Page (565–577)